KIAI'S TRANSFORMATIONAL LEADERSHIP IN IMPROVING THE SOFT SKILLS OF STUDENTS AT ISLAMIC BOARDING SCHOOLS - Olivia, Hibria; Mahtar, Nissa Raziebah (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
This study aims to find out from the results of the development of cottage caregivers in improving the soft skills of students. This research is a qualitative research with a case study conducted at the Nurul Furqon Islamic Boarding School in Malang. The source of informants in this study is students of Pondok Pesantren Nurul Furqon Malang. In this study, what was obtained from informants was in the form of data collection, document analysis, interviews and observations. The results of this study first, give examples of students in polite and wise communication or conversation, secondly provide social skills such as, responsibility, honesty, intelligence in organizing or mixing in society well